IMPROVING STUDENTS’ INTERPERSONAL INTELLIGENCE THROUGH OUTDOOR ACTIVITIES IN LEARNING PLANT MORPHOLOGY : A QUASI EXPERIMENT - Lismaya, Lilis (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This research is motivated by learning that is still done in the classroom only, students feel bored in the classroom for the sake of achieving learning goals, besides that there is still an assumption that interpersonal intelligence of students of biology education is still low, as evidenced by students' inability to interact or socialize quickly with others, lack of social care for others (individualists). The purpose of this study was to analyze the Interpersonal Intelligence of Biology Education Study Program students through Outdoor Activities. The population were all students in semester 2 of Biology Education Study Program FKIP UNIKU in the 2017/2018 academic year as many as 104 students. Samples taken by purposive sampling were 1 experimental class totaling 24 students. The research method used is weak experiment with research designusing The One-Group Pretest-Posttest Design. The data obtained were analyzed using the t test. In addition, the N-gain value was also analyzed, in the experimental class N-gain value was in the medium category. Thus H1 is accepted, meaning that there is a significant effect of outdoor activities on student interpersonal intelligence in plant morphology courses.